PEMBELAJARAN SASTRA MULTIKULTURAL DI SEKOLAH: APLIKASI NOVEL BURUNG-BURUNG RANTAU (Universitas Muhammadiyah Surakarta, 2007)
The learning of multiculturalism opens onesâ fundamental reality in society. Thisarticle aims to describe the learning of multicultural literature at school with applyingto novel âBurung-burung Rantauâ (BbR), a work of Y.B. Mangunwijaya inSemiotics analysis. Indonesian multicultural literature is expected from the processof âIndonesianisationâ from many good cultural expressions of local colour, nation,and global-universal. With enthusiasm of posmodernisme, multicultural literaturecan pierce religion limit, culture, class, ethnic, and nation. Novel BbR expressesbrainchild multicultural past event of tissue and actors: Anggi, Neti, Bowo, andCandra. Brainchild multiculture in BbR among others covers: (1) the born of generationpost-Indonesia in educations values of multiculture, (2) the present generationthat flies freely to every where even to the foreign state or to their own world,(3) the escape from the tradition ties and local cultures even from their nationalculture so they have freedom in creativity, (4) the melting of local and nationalculture, west and east, (5) education values of multicultural pierce in ethnic limits,religion, nationality, class, and gender. Learning of multicultural literatures leadsto harmony with cultures of social transformation existences and life value changesto global culture. For that case, immediate literature teachers are needed to realizethe multicultural paradigms.